Oxidative stress and proteolysis system in type 2 diabetes - D. A. Dyakov; O. E. Akbasheva (Сахарный диабет, 2022)
Background: In establishing the diagnosis — type 2 diabetes, there is a trend of multiple increases every year, which is a health issue. According to the state register, the statistics of patients with diabetes in Russia is about 17% of the total population of the country. The prevalence of diabetes is steadily increasing every year. Today, diabetes mellitus is the leader among the prevalence of non-communicable diseases after cancer, cardiovascular diseases, often leading to disability and death.Aim: To study the relationship between oxidative stress and the «proteinase-inhibitor» system in diabetes mellitus 2.Materials and methods: An observational single-center single-stage sample study was conducted with the participation of patients with type 2 diabetes mellitus and a control group (practically healthy individuals). the activity of elastase-, trypsin-like proteinases, α1-proteinase inhibitor, the content of bityrosine as an indicator of oxidative modification of proteins and the state of lipid peroxidation were determined by spectrophotometric method in all subjects in blood plasma: the concentrations of TBK-active products and antioxidants-the activity of superoxide dismutase, catalase.Results: It was shown that in type 2 diabetes mellitus, the content of TBA of active products (an indicator of lipid peroxidation) increases by 2.34 times and the concentration of bityrosine — an indicator of oxidative modification of proteins, which was negatively dependent on the activity of a proteinase inhibitor (-0.79, p=0.03) increases by 7 times. A decrease in the activity of the proteinase inhibitor (by 23%) was accompanied by an increase in the activity of elastase — and trypsin-like proteinases, respectively, by 1.2 and 2.3 times, compared with practically healthy individuals. The activity of antioxidant enzymes, superoxide dismutase and catalase increased by 8.2 and 6.4 times, respectively.Conclusion: An increase in oxidative stress and oxidative modification of proteins is accompanied by a decrease in the activity of the proteinase inhibitor and an increase in the activity of elastase-, trypsin-like proteinases, as well as antioxidant enzymes.